Classification of Services in the Digital Economy - Weber, Rolf H.; Burri, Mira.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The classification of services in the digital economy proves critical for doing business, but it appears to be a particularly complex regulatory matter that is based upon a manifold set of issues. In the context of the General Agreement on Trade in Services (GATS), when the services classification scheme was drafted in the early 1990s, convergence processes had not unfolded yet and the internet was still in its infancy and not a reality in daily life. Therefore, policy makers are now struggling with the problem of regulating trade in electronic services and are in search of a future-oriented solution for classifying them in multilateral and preferential trade agreements.
IT Services, Telecommunications and New Media in a Converging Era -- Overview of Services Classifications and the Role of Services Classifications -- ICT Services Classification -- Conclusions -- Justification of Trade Restricting Rules (Article XIV GATS).
Keywords: Law; Law; Private International Law, International & Foreign Law, Comparative Law